POLITIK MULTIKULTURALISME DALAM KONTEKS MASYARAKAT MAJEMUK - Pinontoan, Denni H. R. (Tumou Tou, 2020)
This article discusses the reality of diversity by using the concept of "multiculturalism". In political projects, multiculturalism includes the constitutional-based civil society movement fighting for equality and justice. In the context of Indonesia, Pancasila and the 1945 Constitution are the basis of a multicultural political constitution. The discussion on constitutional-based multiculturalism politics then becomes a kind of theory to understand the practice of multiculturalism in the context of North Sulawesi. In the midst of the outbreak of the practice of identity politicization, the civil society movement that pays attention to the politics of multiculturalism is important to be used as an important issue in the diversity management discourse at the local leve